Exposure sources of perfluoroalkyl acids and influence of age and gender on concentrations of chlorinated polyfluorinated ether sulfonates in human serum from China. (May 2020) - Jin, Hangbiao; Lin, Shu; Dai, Wei; Feng, Lingfang; Li, Tao; Lou, Jianlin; Zhang, Quan
Graphical abstract: Highlights: PFCAs and PFSAs in human serum were mainly from direct exposure. The mean 6:2Cl-PFAES serum concentration was higher than PFOA. 6:2Cl-PFAES concentrations in male serum significantly increased with age. 6:2Cl-PFAES concentrations were positively correlated with PFOS in human serum. Abstract: The presence of perfluoroalkyl acids (PFAAs) and chlorinated polyfluoroalkyl ether sulfonates (Cl-PFAESs) in humans has attracted great attention in recent decades. However, information on their exposure sources and the influence of age and gender on Cl-PFAES concentrations in human serum is still limited. In this study, eighty-five serum samples were collected from the general population in Anji, China, and analyzed for perfluoroalkyl carboxylates (PFCAs), perfluoroalkyl sulfonates (PFSAs), and Cl-PFAESs. Perfluorooctane sulfonate (PFOS; mean, 5.9 ng/mL) and perfluorooctanoate (PFOA; 3.3 ng/mL) were the predominant PFAAs in human serum. The serum concentrations of C8 –C12 PFCAs, perfluorohexane sulfonate, and PFOS were significantly ( r s = 0.40–0.98, p < 0.01) correlated with one another. In human serum, the mean percentages of branched isomers for PFOA, perfluorohexane sulfonate, and PFOS were 97.3%, 92.6%, and 66%, respectively. These results suggest that the major source of PFCAs and PFSAs in human serum was direct exposure. The mean 6:2Cl-PFAES (6.0 ng/mL) serum concentration was higher than PFOA ( p < 0.01). The mean 6:2Cl-PFAES concentrations in male and female serum were 6.5 ng/mL and 5.6 ng/mL, respectively. A significant increase in 6:2Cl-PFAES concentrations with age was found in males ( r s = 0.50, p = 0.001). The 6:2Cl-PFAES concentration was positively correlated with C8 –C12 PFCAs and PFOS in human serum ( r s = 0.44–0.91, p < 0.01), indicating that they may have common exposure sources. Overall, this study first investigated the roles of age and gender on human serum concentrations of Cl-PFAESs and provided baseline information on the occurrence of Cl-PFAESs in the general Chinese population.